2018
DOI: 10.1111/jeu.12627
|View full text |Cite
|
Sign up to set email alerts
|

Hv1 Proton Channels in Dinoflagellates: Not Just for Bioluminescence?

Abstract: Bioluminescence in dinoflagellates is controlled by H 1 proton channels. Database searches of dinoflagellate transcriptomes and genomes yielded hits with sequence features diagnostic of all confirmed H 1, and show that H 1 is widely distributed in the dinoflagellate phylogeny including the basal species Oxyrrhis marina. Multiple sequence alignments followed by phylogenetic analysis revealed three major subfamilies of H 1 that do not correlate with presence of theca, autotrophy, geographic location, or biolumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Homologs of the mammalian voltage-gated H + channel, H v 1, are present in coccolithophores and a range of other phytoplankton, although the large outward H + currents typical of C. braarudii have not been reported in other algal cells, suggesting that H + channels are utilized for alternative roles in noncalcifying cells [e.g., in supporting NADPH oxidase activity ( 43 ) or in dinoflagellate bioluminescence ( 44 , 45 )]. We previously characterized Hv1 channels from E. huxleyi and C. braarudii ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…Homologs of the mammalian voltage-gated H + channel, H v 1, are present in coccolithophores and a range of other phytoplankton, although the large outward H + currents typical of C. braarudii have not been reported in other algal cells, suggesting that H + channels are utilized for alternative roles in noncalcifying cells [e.g., in supporting NADPH oxidase activity ( 43 ) or in dinoflagellate bioluminescence ( 44 , 45 )]. We previously characterized Hv1 channels from E. huxleyi and C. braarudii ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…TolQ from A. aeolicus, which diverged very early in evolution, i.e.~3.9 Gya, has a sequence similarity of 22.3% and an amino acid identity of 11% with the proton-gated Hv1 channel from Karlodinium veneficum (Dinoflagellata). This channel is perfectly selective to protons and recent findings suggest that Hv1 channels in these basal organisms have functions separate from only its role in bioluminescence and thus it has been suggested that Hv1 has an ancestral function in dinoflagellate biology [55]. Considering this similarity between two distant proteins but sharing a common function, which is to allow proton fluxes, we asked if this sequence similarity is conserved in the earlybranching archaeon Methanopyrus.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, both bacteria and protists are excitable cells that perceive and propagate stimuli through voltage-gated ion channels similar to those of the animal nervous systems [ 267 , 394 ]. For example, a recent study showed that the diverse families of dinoflagellate H v 1 proton channels that were initially thought to control bioluminescence may also play diverse cellular roles [ 395 ]. Molecular networks in the cells have probably evolved to integrate the multiple stimuli and mediate complex behavioural responses such habituation, associative learning or decision-making, abilities suitable for the establishment of elaborate modes of communication [ 26 , 27 , 28 , 29 , 396 ].…”
Section: Hypothesis: Bioluminescence Signalling In the Unicellular Worldmentioning
confidence: 99%